Optimasi Kebutuhan Gizi untuk Balita Menggunakan Hybrid Algoritma Genetika dan Simulated Annealing - Fitri Anggarsari; Wayan Firdaus Mahmudy; Candra Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
The nutritional state of a person is basically influenced by dietary behavior so that the quantity and quality of the food and beverages consumed has an impact on a person health. Balanced nutrition plays an important role in the growth, physical development, and intelligence of all people, including toddlers, children, and adults. Nutrition in toddlers should be considered because at that time they growth and develope so rapid and prone to occur bad things such as infections that can cause chronic illness, obesity and even death. In this research, we implement hybrid genetic algorithm and simulated annealing to know optimize nutrition requirement on food composition for toddlers. There are two segments of the chromosomal representation that is used in this research, the first segment uses the integer number and the second segment uses the real code number. We use extended intermediate crossover method and random mutation method for the reproduction process. The test resulted in the highest average fitness value of 0.10106 with the best parameters are population = 100, generations = 50, combination between Cr and Mr = 0.8 and 0.3, value of alpha = 0.8, value of T0 = 2 and value of Tn = 0.2. The results of this study is recommendations of foodstuffs according to the nutritional needs that approached the actual needs of the toddlers by considering the weight of food and the minimum price in one day.